Diurnal Variation of Intravenous Thrombolysis Rates for Acute Ischemic Stroke and Associated Quality Performance Parameters - Reuter, Björn; Sauer, Tamara; Gumbinger, Christoph; Bruder, Ingo; Preussler, Stella; Hacke, Werner; Hennerici, Michael G.; Ringleb, Peter A.; Kern, Rolf; Stock, Christian, Stroke Working Group of Baden-Wuerttemberg (Frontiers in Neurology, 2017)
Introduction: Based on data from the Baden-Wuerttemberg stroke registry, we aimed to explore the diurnal variation of acute ischemic stroke (IS) care delivery. Materials and Methods: 92,530 IS patients were included, of whom 37,471 (40%) presented within an onset-to-door time (ODT) ≤4.5h. Daytime was stratified in 3h time intervals and working vs. non-working hours. Stroke onset and hospital admission time, rate of door-to-neurological examination time ≤30min, onset-/door-to-imaging time, IV thrombolysis (IVT) rates, and onset-/door-to-needle time were determined. Multivariable regression models were used stratified by stroke onset and hospital admission time to assess the relationship between IVT rates, quality performance parameters, and daytime. The time interval 00:00 to 03:00 and working-hours, respectively, were taken as reference. Results: The IVT rate of the whole study population was strongly associated with the sleep-wake cycle. In patients presenting within the 4.5h time window and potentially eligible for IVT stratification by hospital admission time identified two time intervals with lower IVT rates. First, between 03:01 and 06:00 (IVT rate 18%) and likely attributed to in-hospital delays with the lowest diurnal rate of door-to-neurological examination time ≤30min and the longest door-to-needle time. Second, between 06:01 and 15:00 (IVT rate 23-25%) compared to the late afternoon and evening hours (IVT rate 27-29%) due to a longer onset-to-imaging and door-to-imaging time. No evidence for a compromised stroke service during non-working hours was observed. Conclusions: The analysis provides evidence that acute IS care is subject to diurnal variation which may affect stroke outcome. An optimization of IS care aiming at constantly high IVT rates over the course of the day therefore appears desirable.